The Use of Scaffolding Strategies to Enhance Pre-Numeracy Skills among Preschool Children - Nair, Subadrah Madhawa; Marimutthu , Thirumani; Krishnasamy, Hariharan N; Singh, Gurdip Kaur Saminder; Siddique, Muhammad (Journal of Ecohumanism, 2024)
Purpose: This research was designed to study how the teacher uses scaffolding strategies in teaching pre-numeracy skills among preschool children. Methodology: The qualitative study has employed the phenomenology research design. The sample comprised five preschool children and a pre-school teacher from a private preschool at Klang district in Selangor. Purposive sampling was employed in choosing the sample. Three instruments were used to investigate the children performance level and to identify how the scaffolding strategies employed by the teacher helped to enhanced preschool children’s pre-numeracy skills. The instruments were classroom observation checklist, document analysis (namely children’s worksheet) and face to face interviews with the teacher. Five classroom observations were conducted by the researchers to collect the data. Findings: Results of the document analysis and the observations (ten observations) indicated that the teacher used excavating, modelling, guiding, focusing, and extending scaffolding strategies to enhance the children’s pre-numeracy skills. In addition, the children learned very fast when their engagement improved and they were willing to learn in an atmosphere of fun and excitement. The findings also revealed that these strategies are effective in helping the children to master the pre-numeracy skills and their level of performance improved. Conclusion: This study has crucial practical implications whereby the results suggest that The Ministry of Education can train preschool teachers to employ scaffolding strategies to teach numeracy skills. In term of pedagogical implication preschool teachers can use scaffolding strategies as an alternative method to assist students in mastering numeracy skills. Contribution/Originality: This study provides valuable insights on how to use various scaffolding strategies (excavating, modelling, guiding, focusing, and extending) to enhance the children’s pre-numeracy skills. These strategies seem to be effective in helping children to master pre-numeracy skills.